DESAIN MEDIA KOMUNIKASI VISUAL PENUNJANG EVENT WISUDA - Triyono Triyono; Kemal Salahuddin; Hendi Setiawan (CCIT Journal, 2017)
Graduation organizing events in an educational institution is the most awaited moment by the student who has completed the learning. That Moment is the awarding accordance to each education level. STMIK Raharja is a computer-based educational institution in Tangerang city which organizes Graduation event for Diploma and Bachelor's Degree annually. The implementation of the graduation is the biggest event to the colleges therefore the preparation is organized carefully starting from the committee formation. Refer to this event so that required a new media visual communication to support the implementation runs attractive and successful. This event is held not only to reward graduates but also to promote the college to invited guests or public. The aims of this study is to determine the media used to be effective in organizing events and drafting Graduation visual communication media to support the event as an image of the college. The methodology used is objective visual, strategy visual, copy writing, art directing and rough layout designing, comprehensive layout, and final artwork . The media visual communication are designed to 9 items such as banners outside and inside, banners up and down, Backdrop, Invitation Cards and contents of the invitation, book Cover, media advertised of Greetings & Success addressed to Graduations in mass media and souvenir such as fans and glasses.